Kesulitan-Kesulitan Guru IPS Dalam Penilaian Autentik - Ranti Nazmi (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2017)
The objective of the research is to find out the relationships between the performance of the young and sport department with the achievement central education and sport training players (PPLP).The research was conducted at the Nourth Maluku with the totaly sample.The results of the research concludes that there are positive relationship between Performance of the young and sport department with the achievement of central education and sport training players (PPLP). Furthermore, there is positive relationship between performance of the young and sport department and society perception together with the achievement of central education and sport training players (PPLP).